Palaeokarst Deposits in Caves: Examples from Eastern Australia and Central Europe - Osborne, Armstrong R.L. (Acta Carsologica, 2017)
Palaeokarst deposits are most commonly found in excavations, drill holes and naturally exposed at the Earth’s surface. Some caves however intersect palaeokarst deposits. This occurs in large hypogene caves in the USA, thermal caves in Hungary and in many caves in eastern Australia. Palaeokarst deposits in caves respond to cave forming processes in the same way as hostrock: the palaeokarst deposits form cave walls. A range of palaeokarst deposits is exposed in caves including; filled tubes, walls composed of flowstone, large-scale bodies, breccia pipes, dykes, volcaniclastic palaeokarst and crystalline palaeokarst. As well as being exposed in cave walls, palaeokarst deposits can wholly or partly form speleogens (speleogens made from palaeokarst). Records of geological events not preserved elsewhere can occur in palaeokarst deposits in caves. These can be difficult to correlate with conventional geological histories. It is important to be able to distinguish between palaeokarst deposits, relict sediments and phantom rock (in-situ weathered rock, also called ghost rock; Vergari & Quinif 1997). Relict sediments can be distinguished from palaeokarst deposits because the cave walls bound relict sediments while palaeokarst deposits form the cave walls. Palaeokarst can be distinguished from phantom rock, as palaeokarst is unconformable with the hostrock, with structures in the hostrock not continuing across the boundary into the palaeokarst. Hostrock structures and textures do continue across the boundary between unaltered hostrock and phantom rock. Similarly, cave sediments are unconformable or disconformable with the hostrock while phantom rock is conformable with hostrock containing hostrock structures and textures. It has been difficult to explain why palaeokarst occurs in some caves and not others. One explanation worth considering is that palaeokarst deposits are not intersected by caves or sections of caves that contain large perennial streams and/or have undergone large-scale vadose fluvial development capable of escaping from the bounds of structural guidance, such as the caves in the Classical Karst. Key words: palaeokarst, caves, Australia, relict sediments, phantom rock.